Three-dimensional reconstructions of haustoria in two parasitic plant species in the Orobanchaceae. Issue 4 (25th January 2021) - Masumoto, Natsumi; Suzuki, Yuki; Cui, Songkui; Wakazaki, Mayumi; Sato, Mayuko; Kumaishi, Kie; Shibata, Arisa; Furuta, Kaori M; Ichihashi, Yasunori; Shirasu, Ken; Toyooka, Kiminori; Sato, Yoshinobu; et al.
Abstract: Parasitic plants infect other plants by forming haustoria, specialized multicellular organs consisting of several cell types, each of which has unique morphological features and physiological roles associated with parasitism. Understanding the spatial organization of cell types is, therefore, of great importance in elucidating the functions of haustoria. Here, we report a three-dimensional (3-D) reconstruction of haustoria from two Orobanchaceae species, the obligate parasite Striga hermonthica infecting rice ( Oryza sativa ) and the facultative parasite Phtheirospermum japonicum infecting Arabidopsis ( Arabidopsis thaliana ). In addition, field-emission scanning electron microscopy observation revealed the presence of various cell types in haustoria. Our images reveal the spatial arrangements of multiple cell types inside haustoria and their interaction with host roots. The 3-D internal structures of haustoria highlight differences between the two parasites, particularly at the xylem connection site with the host. Our study provides cellular and structural insights into haustoria of S. hermonthica and P. japonicum and lays the foundation for understanding haustorium function. Abstract : Three-dimensional image reconstruction visualized the spatial organization of cell types in the haustoria of the Orobanchaceae parasitic plants Striga hermonthica and Phtheirospermum japonicum .